Zimbabwe's Exodus : Crisis, Migration, Survival - Tevera, Daniel S.; Crush, J. S. (Book collections on Project MUSE., 2010)
This book includes personal stories of ordinary Zimbabweans living and working in other countries, who describe the hostility and xenophobia they often experience. --Book Jacket.